Malaysian ESL teachers’ practice of written feedback on students’ writing - Razali, Khairil Azwar; Abdul Rahman, Zainurin; Sheikh Ahmad, Ismail; Othman, Joharry (UPM Press, 2021)
Feedback to students’ writing plays an important role as a scaffolding technique to help the students to improve their writing skills. With the introduction of school-based assessment and the Common European Framework of Reference (CEFR) into the new Standards-based English Language Curriculum (SBELC), teachers are expected to adapt the process writing approach in their classroom, where feedback is at the core of the process writing approach. This present study aims to explore Malaysian ESL teachers’ practice of written feedback in their writing classrooms. Two sample essays were used in this study. The sample essays were written by a Form Three student of a secondary school in Kuantan, Pahang, and a Form Five student from a secondary school in Manjung, Perak. The sample essays were sent to all secondary schools in Pahang, and teachers who teach the English Language at the schools were asked to mark the essay as how they would normally mark their students’ essays. The participants of this study were selected using purposive sampling. A total of 89 student sample essays with the teachers’ marking were returned, and the teachers’ feedback were analysed. This study found that most of the participants mark their students’ essays comprehensively and implicitly. However, some of the respondents did not give any feedback at all, and even if they did, the feedback would be retracted from the marking rubric. It has also been found that the respondents of this present study did not utilise comments on goals to work towards or specific activities for improvement. This paper further discusses the findings in view of the assessment of learning (AfL) and gives recommendations for future practice.